(untitled) (Revista Archai, 2022)
In Laws, mousike is restored to the constitution of the city (Magnesia) as an instrument for the education of citizens. According to the Athenian Stranger, the regulation and preservation of mousike’s correct forms, through melos and schema, is also responsible for the maintenance of Magnesia’s cultural and political stability. In this context, Plato praises Egyptian art, which would have maintained its style and, consequently, Egyptian politics stable for a long time. This article will thus present a translation of 653c - 654a and three contemporary interpretations of this eulogy. Lastly, the three interpretations will be evaluated and a possibility of an approximation between the Platonic praise and (visual) Egyptian art will be suggested, considering its probable social, religious and political functions.